2011
DOI: 10.4018/ijmmme.2011070105
|View full text |Cite
|
Sign up to set email alerts
|

Roughness Optimization of Electroless Ni-B Coatings Using Taguchi Method

Abstract: In this paper, the authors present an experimental study of roughness characteristics of electroless Ni-B coatings and optimization of the coating process parameters based on L27 Taguchi orthogonal design. Three coating process parameters are considered viz. bath temperature, reducing agent concentration, and nickel source concentration. It is observed that concentration of reducing agent together with bath temperature play a vital role in controlling the roughness characteristics of the coatings. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Grey analysis is employed together with Taguchi method for the optimization and it was found that concentration of the reducing agent and its interaction with concentration of the nickel source solution, have significant influence in controlling the roughness characteristics of the coating. Similar study is carried out for Ni-B coating (Das & Sahoo, 2011h) and concentration of reducing agent and nickel source is observed to have good amount of significance on the roughness. Incorporation of tungsten ion is found to influence the roughness characteristics of Ni-P coatings significantly (Roy & Sahoo, 2012b).…”
Section: Obtaining Smoother Surfacesupporting
confidence: 62%
See 3 more Smart Citations
“…Grey analysis is employed together with Taguchi method for the optimization and it was found that concentration of the reducing agent and its interaction with concentration of the nickel source solution, have significant influence in controlling the roughness characteristics of the coating. Similar study is carried out for Ni-B coating (Das & Sahoo, 2011h) and concentration of reducing agent and nickel source is observed to have good amount of significance on the roughness. Incorporation of tungsten ion is found to influence the roughness characteristics of Ni-P coatings significantly (Roy & Sahoo, 2012b).…”
Section: Obtaining Smoother Surfacesupporting
confidence: 62%
“…Taguchi technique 28 (Arun & Kumar, 2013;Cai,Yan, & Shi,2012;Das & Sahoo, 2011a;Das & Sahoo, 2011b;Das & Sahoo, 2012;Das & Sahoo, 2011d;Das & Sahoo, 2011e;Das & Sahoo, 2011j;Deng & Moller, 1992;Farzaneh, Ehteshamzadeh, & Mohammadi, 2011;Farzaneh, Ehteshamzadeh Ghorbani, & Mehrabani, 2010;Hosseini & Bodaghi, 2013, Hou, Xiao, Guo, Zhou, & Wang, 2013Jiang, Xiao, Hu, Peng, Zhang, & Wang, 2009;Jiang & Xiao, 2011;Jiang, Kan, Yuen, & Wong, 2008;Li & Liu, 2011;Lin, Xuanmin, Jian, & Shixi, 2008;Liu, Zhang, Yu, & Ning, 2011;Panja & Sahoo, 2014;Perumalraj & Dasaradan, 2011;Qu, Huang, & Cai, 2011;Roy & Sahoo, 2013a;Sahoo, 2008a;Sahoo, 2008b;Sahoo, 2008c;Sahoo, 2009;Wang, Hu & Li, 2012) Response surface methodology 5 (Georgieva & Armyanov, 2007;Guo, Jiang, Yuen, Ng & Lan 2013;Oraon, Majumdar & Ghosh, 2006;Oraon, Majumdar & Ghosh 2007;Oraon, Majumdar & Ghosh, 2008) Grey relational analysis 13 (Das & Sahoo, 2011c;Das & Sahoo, 2011f;Das & Sahoo, 20...…”
Section: Optimization Techniques No Of Studies Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of SPB of grade 410 martensitic stainless steel could be considered as a multi-input process with multiple outputs and parameter design can be performed by using techniques like data envelopment analysis, grey relational analysis (GRA), desirability analysis, principal component analysis (PCA), fuzzy logic and artificial neural networks (ANN) (Krishnaiah and Shahabudeen, 2012). The orthogonal arrays and signal-to-noise (S/N) ratio were adopted in Taguchi's optimization strategy (Das and Sahoo, 2011). However Taguchi techniques were employed for single response optimization problem, while a manufacturing situation generally requires the simultaneous optimization of multiple responses.…”
Section: Introductionmentioning
confidence: 99%